IDENTIFIKASI FAKTOR KUNCI DALAM PEMANFAATAN PELAYANAN POSYANDU OLEH IBU BALITA - Maratning, Anastasia; Rialita, Metri; Nursery, Septi Machelia Champaca; Dias, Maria Frani Ayu Andari; Martini, Margaretha; Ivana, Theresia; Sitompul, Dania Relina (STIKES Suaka Insan, 2024)
It is important to improve the optimal utilization of posyandu services by mothers of children under five. An extensive health center in North Barito District, Central Kalimantan-Indonesia, revealed that the current utilization of Posyandu is only 43.91%, falling short of the Health Office's target of 80%. This study aims to identify the factors that influence mothers of young children to use Posyandu services. The research methodology involved a descriptive survey using a cross-sectional approach. It included a sample of 95 mothers of toddlers from all Posyandu in Muara Teweh Health Centre, selected using a disproportionate stratified random sampling method. The study utilized a questionnaire as the primary instrument, and the collected data was analyzed and presented as frequency distribution tables. The findings indicated that 62.11% of the 95 mothers had a good level of knowledge about posyandu for toddlers, 75.79% found the home distance and transportation to the posyandu affordable, 55.79% received family support to attend posyandu, and 69.74% acknowledged the active role played by cadres in facilitating posyandu. It is evident that continuous and organized support from all sectors is crucial to ensure optimal and increased utilization of posyandu.